Plants in the real world: An introduction to the JBC Reviews thematic series - Jez, Joseph M. (J Biol Chem, 2020)
The deep relationship between plants and humans predates civilization, and our reliance on plants as sources of food, feed, fiber, fuels, and pharmaceuticals continues to increase. Understanding how plants grow and overcome challenges to their survival is critical for using these organisms to meet current and future demands for food and other plant-derived materials. This thematic review series on “plants in the real world” presents a set of eight reviews that highlight advances in understanding plant health, including the role of thiamine (vitamin B(1)), iron, and the plant immune system; how plants use ethylene and ubiquitin systems to control growth and development; and how new gene-editing approaches, the redesign of plant cell walls, and deciphering herbicide resistance evolution can lead to the next generation of crops.